2011
DOI: 10.1074/jbc.m111.220434
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the HIV-1 gp120 Viral Protein V3 Loop with Bacterial Lipopolysaccharide

Abstract: HIV-1 represents an elusive target for therapeutic compounds due to its high rate of mutation. Targeting

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…Microbiota can influence viral infection through direct and/or indirect mechanisms on the host and/or virus, making a mechanistic search akin to “finding a needle in a haystack.” However, previous studies may inform future studies and help limit the search. There are two common themes that have emerged: 1) Microbial products initiate innate immune signaling to limit or promote viral infection (3740, 44, 49), and 2) Microbial products interact with viral particles to alter infectivity or host responses (31, 46, 49, 60, 67). Interestingly, bacterial LPS binds poliovirus (31, 46), MMTV (49), and HIV (67), suggesting that LPS binding may be a property shared by several viruses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microbiota can influence viral infection through direct and/or indirect mechanisms on the host and/or virus, making a mechanistic search akin to “finding a needle in a haystack.” However, previous studies may inform future studies and help limit the search. There are two common themes that have emerged: 1) Microbial products initiate innate immune signaling to limit or promote viral infection (3740, 44, 49), and 2) Microbial products interact with viral particles to alter infectivity or host responses (31, 46, 49, 60, 67). Interestingly, bacterial LPS binds poliovirus (31, 46), MMTV (49), and HIV (67), suggesting that LPS binding may be a property shared by several viruses.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that microbiota enhance HIV pathogenesis. Second, Majerle et al demonstrated that the HIV envelope protein gp120 binds bacterial LPS and that LPS-bound gp120 has reduced binding to target cells (67). These results suggest that microbial products may reduce HIV infection.…”
Section: Unclear Effects Of the Microbiota On Virusesmentioning
confidence: 99%
“…Thus, it is possible that the immune activation coinciding with HIV‐1 infection is required for productive infection of the target cells. Furthermore, there may be a direct interaction between the virus and LPS, as HIV‐1 gp120Env binds LPS in vitro . Therefore, it is possible that HIV and SIV may also take advantage of commensal bacteria to assure successful propagation and spread.…”
Section: The Host's Microbiota Facilitates Viral Replication and Pathmentioning
confidence: 99%
“…These include developing anti-HIV drugs [18,19], evaluating antiviral activities of multivalent anionic porphyrins [20], bacterial lipopolysaccharide [21], or Epap-1 [22], and the anti-V3 immune response investigations [23-26]. Early study demonstrated that the cyclic V3-loop-related HIV-1 conjugate vaccines elicited neutralizing antibodies [27].…”
Section: Introductionmentioning
confidence: 99%